The introduction strategy of the emerging online marketplace considering risk attitude and channel power. Issue 5 (3rd July 2020) - Chen, Huiru; Hao, Yifei; Yan, Yingchen
Abstract : With the development of online retailing, traditional online platforms have begun to offer a novel online marketplace format that brings many advantages but also gives rise to problems such as operational risks and changes in channel power. This paper studies whether the e-tailer and manufacturer can reach a consensus on introducing the marketplace channel and obtains the following insights. First, the manufacturer always prefers to introduce the online marketplace in the model where she acts as the leader. The e-tailer has the same preference for the online marketplace when he moves later or simultaneously with the manufacturer. Second, as the participants become more risk-averse, the manufacturer and e-tailer would be less willing to introduce the online marketplace, and it would be more difficult to realize the equilibrium strategy under all power structure models. Third, by combining the cross-effect of the attitude towards risks and the power structure, we find that when the participants prefer risks and the e-tailer has strong channel power, it would be much easier for the two parties to reach a consensus about introducing the online marketplace.